Komunikasi Ritual Dalam Upacara Piodalan Di Pura Luhur Giri Salaka Alas Purwo Kecamatan Tegaldlimo Kabupaten Banyuwangi - Eria Meta Setiyana; I Wayan Wirata; I Made Agus Yudiarsana (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
Pura Luhur Giri Salaka Alas Purwo has several uniqueness, one of which is the piodalan ceremony along with the pagerwesi holiday. besides that the piodalandi ceremony of Pura Luhur Giri Salaka Alas Purwo still maintains the use of the tradition of tumpengan or slametan at the Kawitan Site as a native culture of the Banyuwangi Hindu community. In this study, three problems were formulated as follows: 1) What is the form of ritual communication in the Piodalan Ceremony; 2) How is the process of implementing the Piodalan Ceremony; 3). What are the implications of the implementation of the Piodalan Ceremony in Luhur Giri Salaka Alas Purwo Temple? This study uses a descriptive qualitative approach using informants such as: religious leaders, community leaders, youth leaders, women leaders, temple managers and Hindu communities in general. Data collection techniques used are non-participant observation, interviews and documentation. The data obtained were then analyzed through three stages: reduction, presentation of data and then inference. The theory used to dissect the existing problem formulation is Talcott Parsons Functional Structure, I.B Tylor's Religious Theory and Max Weber's Social Action Theory. The results of the study are as follows: 1) Forms of Ritual Communication in the Piodalan Ceremony at Luhur Giri Salaka Alas Purwo Temple include: a). Transcendent Communication; b). Social Communication; c). Human Communication with the Environment. 2) The process of carrying out the piodalan ceremony, which is 4 days from Wednesday, the peak of the event, which is the piodalan ceremony and pagerwesi, Thursday-Friday devotions, and on Saturday, the sellers of offerings or offerings are used by a combination of Javanese and Balinese; 3). Implications of the Implementation of the Piodalan Ceremony in Luhur Giri Salaka Alas Purwo Temple, there are four of them: a). Actions of Intrumental Rationality; b) Value Rational Actions; c) Affective Actions and; d). Traditional Action Hindu communities in Banyuwangi always offer prayers at the kawitan site first.